Effects of core and dynamic balance training on motor characteristics in Turkish basketball league players - Kiratli, Tuncay; Yildirim, Yavuz; Şahin, Cihad; Saritemur, Büşra (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to investigate the effects of 8 weeks of core and dynamic balance training on reaction speed and agility in A-team basketball players. A total of 29 male basketball players participated in the study, with athletes divided into two groups: experimental (n=14) and control (n=15). The experimental group received core and dynamic balance training three days a week in addition to technical and tactical basketball training for 8 weeks, while the control group received only technical and tactical training for the same duration. Body fat percentage (measured with Tanita BC 418-ma), the lane agility drill, and reactive shuttle run tests were conducted before and after the training as performance measurements. When analyzing the pre-test and post-test results regarding the effects of core and dynamic balance training on the motoric characteristics of players in the Turkish Basketball League, no significant difference was found in the Reactive Shuttle Run test for the experimental group (p<0.05). However, significant differences were observed in both the experimental and control groups for the other tests (p>0.05). The findings indicated that core and dynamic balance exercises, when added to basketball training, did not show an additional effect on the athletes in the experimental group, unlike the control group. However, no difference was found in the results of the Reactive Shuttle Run test between the two groups.